Essential oil diversity of Origanum vulgare L. populations from Southern Italy. (15th November 2017) - Mastro, Giuseppe De; Tarraf, Waed; Verdini, Leonardo; Brunetti, Gianluca; Ruta, Claudia
Highlights: Essential oil diversity in Origanum vulgare L. from Calabria Region was exhibited. Cymyl compounds and acyclic linalool/linalyl acetate were the two main chemotypes. Sustainable collection of Origanum vulgare L. chemotypes for new and specific uses. Abstract: Essential oils (EOs) belonging to 25 wild populations of Origanum vulgare L. samples, growing wild in different locations of Calabria Region (Southern Italy), were analyzed using gas chromatography–mass spectrometry. The quantitative and qualitative data showed EO concentrations ranging from 0.96 to 5.10% and 37 compounds detected, representing more than 80% of the total composition of the oils. By applying hierarchical cluster analysis on the basis of the EO constituents, two main groups and three subgroups were found, reflecting the variation in the chemical composition of EOs from wild oregano populations. The first group consisted of acyclic (linalool/linalyl acetate) chemotypes with a predominant presence of linalyl acetate; the second was characterized by chemotypes rich in cymyl-compounds, mainly carvacrol, thymol and γ-terpinene. The data obtained contribute to broaden the inventory of wild oregano populations from Calabria to plan programs for the selection of chemotypes with new and specific uses.